Planet Google - "Stross, Randall E." (New York)
"Includes bibliographical references (p. 201-257) and index. Open and closed -- Unlimited capacity -- The algorithm -- Moon shot -- Gootube -- Small world, after all -- A personal matter -- Algorithm, meet humanity."
Keywords: GOOGLE (FIRM);INTERNET INDUSTRY -- UNITED STATES -- HISTORY.;WEB SEARCH ENGINES -- UNITED STATES -- HISTORY